Catalytic Si/B Exchange Condensation: A Green B–C Coupling Method That Provides Access to Monodisperse (Het)arylborane ‘Trimers’ - Fritze, Lars; Riensch, Nicolas A.; Helten, Holger (Synthesis, 2019)
The potential of our metal-free B–C coupling method using catalytic Si/B exchange condensation is demonstrated by the synthesis of a series of monodisperse (het)arylborane oligomers with four (het)arene moieties and three boron centers (i.e., ‘trimers’). Photophysical and electrochemical investigations evidenced effective π-conjugation over the (het)arene rings and the boron centers.
Keywords: boron; B–C bond formation; furan; thiophene; organocatalysis; organoboranes; monodisperse oligomers; conjugated materials